PELATIHAN DIGITAL MARKETING MENGGUNAKAN APLIKASI WHATSAPP BLAST UNTUK PENINGKATAN KAPASITAS USAHA UMKM DI KOTA DENPASAR - I Kadek Arya Sugianta; Gde Palguna Reganata; I Nyoman Ari Yuda; Rajdev Dillon (Universitas Mataram, 2022)
There are still many UMKM in Denpasar that have not taken advantage of digital advertising opportunities to accelerate growth since the Covid 19 outbreak is limiting all business activities. Data from the Bali Provincial Cooperative and the MSME Office shows that of the total 340 million UMKM units in Bali, only about 250 UMKM are using digital transformation in their business operations. The Covid-19 pandemic has caused sales to drop, with some merchants going bankrupt or temporarily closing. This community service aims to equip UMKM in Denpasar with knowledge and skills on how to use technology to communicate and encourage digital businesses to use the WhatsApp Blast app. The activity uses a participatory approach and personal communication. It consists of 3 stages of training, which are: (1) presentation of materials by the person in charge; (2) training on how to use the WhatsApp Blast application; and (3) consulting and problem solving when doing digital advertising using the WhatsApp Blast application. The results of the training show an increase in the knowledge and skills of UMKM members towards using WhatsApp Blast as a digital marketing and communication medium, which is based on enthusiasm and feedback. positive response of the participants in the training activities. The conclusion of this training was that the provision of training materials and digital marketing helped improve the understanding and skills of UMKM members in using WhatsApp Blast for UMK participants in Denpasar.